Effect of internet-based vs. in-person multimodal interventions on patients with mild to moderate Alzheimer’s disease: a randomized, cross-over, open-label trial - Jung, Young Hee; Park, Sang-Cheol; Lee, Jee Hee; Kim, Myong Jong; Lee, Seunghoon; Chung, Su Jin; Moon, Ji Yeon; Choi, Young Hi; Ju, Jieun; Han, Hyun Jeong; Lee, So Young (Frontiers in Public Health, 2023)
Objective We aimed to investigate the effect of internet-based and in-person cognitive interventions on cognition, mood, and activities of daily living (ADL) on patients with mild to moderate Alzheimer’s disease (AD) and examine whether internet-based intervention is as effective as the in-person intervention. Methods We recruited 52 patients with probable mild AD, of whom 42 completed the trial. We randomly divided participants into intervention and control groups at a 1:1 ratio and statistically compared the neuropsychological test results of the two groups. In addition, patients in the intervention group were randomly assigned to a 4 weeks internet-based or in-person intervention, with subsequent crossover to the other group for 4 weeks. We statistically analyzed and compared the neuropsychological test scores between internet-based and in-person interventions. Results Compared with the control group, the intervention group (internet-based and in-person) showed significantly improved profile in cognition (p < 0.001), depression (p < 0.001), anxiety (p < 0.001) and ADL (p < 0.001). In addition, the effect of the internet-based intervention on cognition (p = 0.918) and depression (p = 0.282) was not significantly different from that of the in-person intervention. However, in the Beck anxiety inventory (p = 0.009) and Seoul instrumental activity of daily living (p = 0.023), in-person intervention was more effective than internet-based intervention. Conclusion This study suggests that both types of cognitive intervention (in-person and internet-based) may be viable supplementary treatments along with approved pharmacological therapy. In terms of anxiety and ADL, the effect of the in-person interventions may be more effective than the-internet based interventions.